Implementasi Asesmen Autentik Kurikulum Merdeka Pada Mata Pelajaran Bahasa Arab SMP Islam Cikal Harapan 1 BSD - Hijjah, Shifany Maulida; Ridlo, Ubaid; Raswan, Raswan (Al-Muyassar: Journal of Arabic Education, 2025)
Merdeka Curriculum aims to make learning more meaningful. In general, this program does not replace the existing program, the main goal is to improve the existing system while offering a simpler learning process. The purpose of this study is to describe the implementation of authentic assessments which include performance assessments, learning projects, written tests, and oral tests conducted by Cikal Harapan 1 BSD Islamic Junior High School teachers in Arabic language subjects. In other words, this research can be a reference to the development of sustainable assessment patterns in the independent curriculum. The implementation of this research uses a descriptive qualitative approach. Descriptive research method. The research data sources are divided into two sources, the first source of literary data, and the second source of field data (field research). The data collection techniques are observation, interviews, and documentation. Data validity techniques researchers use triangulation, there are three triangulations, namely source triangulation, method triangulation, and theory triangulation. The results of this study show that there are several assessment techniques used by teachers in each aspect. In the cognitive aspect, teachers use written tests, oral tests, and assignments. The affective aspect of the teacher uses observation, and daily notes. While the psychomotor aspects teachers use project techniques. Of these three aspects are used to get a complete picture of the achievement of learner competence and can also be used to measure the level of learning success which is very important in education.